2000
DOI: 10.1007/s004250000387
|View full text |Cite
|
Sign up to set email alerts
|

Somatic embryogenesis induced by the simple application of abscisic acid to carrot ( Daucus carota L.) seedlings in culture

Abstract: Seedlings of carrot (Daucus carota L. cv. Red Cored Chantenay) formed somatic embryos when cultured on medium containing abscisic acid (ABA) as the sole source of growth regulator. The number of embryos per number of seedlings changed depending on the concentration of ABA added to the medium, with a maximum embryo number at 1 x 10(-4) M ABA. Seedling age was critical for response to exogenous ABA; no seedling with a hypocotyl longer than 3.0 cm was able to form an embryo. Removal of shoot apices from seedlings… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
59
1
4

Year Published

2004
2004
2019
2019

Publication Types

Select...
3
2
2

Relationship

0
7

Authors

Journals

citations
Cited by 93 publications
(64 citation statements)
references
References 23 publications
0
59
1
4
Order By: Relevance
“…Analysis of the sequenced Arabidopsis genome revealed that a family of five homologs of the carrot SERK was present. Also in maize and Medicago multiple SERK homologs were found three and five, respectively [5,130]. The Arabidopsis SERKI protein contains all the main protein motifs found in other species [66,72,130,198].…”
Section: Serk Genesmentioning
confidence: 99%
See 3 more Smart Citations
“…Analysis of the sequenced Arabidopsis genome revealed that a family of five homologs of the carrot SERK was present. Also in maize and Medicago multiple SERK homologs were found three and five, respectively [5,130]. The Arabidopsis SERKI protein contains all the main protein motifs found in other species [66,72,130,198].…”
Section: Serk Genesmentioning
confidence: 99%
“…In addition, SERK was detected during flower development and was highest 10 days after pollination [173]. Homologs of SERK have been discovered in several plant species, which includes Dactylis glomerata [184], Zea mays [5], Medicago truncatula [130], Helianthus annuus [198], Oryza sativa [79], Citrus unshiu [178], Theobroma cacao [169,170], and Solanum tuberosum [177]. Analysis of the sequenced Arabidopsis genome revealed that a family of five homologs of the carrot SERK was present.…”
Section: Serk Genesmentioning
confidence: 99%
See 2 more Smart Citations
“…The protuberances form at right angles to the hypocotyl growth axis, suggesting that a new growth polarity is established in the presence of ethylene. Hypocotyl protuberances can also be stimulated when carrot (Daucus carota) seedlings are agitated in the presence of abscisic acid (ABA) and, when agitation ceases, these eventually develop into somatic embryos (Nishiwaki et al, 2000). Stimulation of cell proliferation by ABA alone is at odds with ABA's stimulation of the cyclin-dependent kinase inhibitor ICK (Wang et al, 1998), which suppresses G1 to S transitions.…”
Section: Altered Cell Division Polaritymentioning
confidence: 99%